The Na+/Ca2+ Exchanger 3 Is Functionally Coupled With the NaV1.6 Voltage-Gated Channel and Promotes an Endoplasmic Reticulum Ca2+ Refilling in a Transgenic Model of Alzheimer’s Disease - Piccialli, Ilaria; Ciccone, Roselia; Secondo, Agnese; Boscia, Francesca; Tedeschi, Valentina; de Rosa, Valeria; Cepparulo, Pasquale; Annunziato, Lucio; Pannaccione, Anna (Frontiers in Pharmacology, 2021)
The remodelling of neuronal ionic homeostasis by altered channels and transporters is a critical feature of the Alzheimer’s disease (AD) pathogenesis. Different reports converge on the concept that the Na+/Ca2+ exchanger (NCX), as one of the main regulators of Na+ and Ca2+ concentrations and signalling, could exert a neuroprotective role in AD. The activity of NCX has been found to be increased in AD brains, where it seemed to correlate with an increased neuronal survival. Moreover, the enhancement of the NCX3 currents (INCX) in primary neurons treated with the neurotoxic amyloid β 1-42 (Aβ1-42) oligomers prevented the endoplasmic reticulum (ER) stress and neuronal death. The present study has been designed to investigate any possible modulation of the INCX, the functional interaction between NCX and the NaV1.6 channel, and their impact on the Ca2+ homeostasis in a transgenic in vitro model of AD, the primary hippocampal neurons from the Tg2576 mouse, which overproduce the Aβ1-42 peptide. Electrophysiological studies, carried in the presence of siRNA and the isoform-selective NCX inhibitor KB-R7943, showed that the activity of a specific NCX isoform, NCX3, was upregulated in its reverse, Ca2+ influx mode of operation in the Tg2576 neurons. The enhanced NCX activity contributed, in turn, to increase the Ca2+ content of the ER, without affecting the cytosolic Ca2+ concentrations of the Tg2576 neurons. Interestingly, our experiments have also uncovered a functional coupling between NCX3 and the voltage-gated NaV1.6 channels. In particular, the increased NaV1.6 currents appeared to be responsible for the upregulation of the reverse mode of NCX3, since both TTX and the Streptomyces griseolus antibiotic anisomycin, by reducing the NaV1.6 currents, counteracted the increase of the INCX in the Tg2576 neurons. In agreement, our immunofluorescence analyses revealed that the NCX3/NaV1.6 co-expression was increased in the Tg2576 hippocampal neurons in comparison with the WT neurons. Collectively, these findings indicate that NCX3 might intervene in the Ca2+ remodelling occurring in the Tg2576 primary neurons thus emerging as a molecular target with a neuroprotective potential, and provide a new outcome of the NaV1.6 upregulation related to the modulation of the intracellular Ca2+ concentrations in AD neurons.